College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 2, Functions - Chapter 2 Review - Exercises: 5

Answer

g(-1) = 5 g(0) = 0 g(1) = -3 g(2) = -4 g(3) = -3

Work Step by Step

$g(x) = x^{2} - 4x$ Plug in x values into g(x) $g(-1) = (-1)^{2} - 4(-1)$ = 1 + 4 = 5 $g(0) = (0)^{2} - 4(0)$ = 0 - 0 = 0 $g(1) = (1)^{2} - 4(1)$ = 1 - 4 = -3 $g(2) = (2)^{2} - 4(2)$ = 4 - 8 = -4 $g(3) = (3)^{2} - 4(3)$ = 9 - 12 = -3
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.